Effect of different pre-treatments on vacuum oven drying of pegaga (Centella asiatica L.) leaves: drying kinetics, nutritional qualities, and antioxidant capacity - Mohd Yunos, Nazurah; Ariffin, Siti Hajar; Yusof, Yus Aniza; Mohd Salleh, Faiqa Shazeaa; Zakaria, Rabitah (Universiti Putra Malaysia Press, 2025)
Recent reports have indicated that a broad variety of phytochemicals, particularly those with antioxidant activity, can be found in fruits and vegetables, which has drawn considerable interest. However, due to its delicate texture and high water content, it is prone to damage and has a short shelf life. Drying is the most frequent practice for minimizing moisture content and, consequently, water activity to a safe level that extends longevity. The current commercial potential of pegaga, particularly in dried form, has not been adequately investigated. The effect of various pre-treatments (water blanching, steam blanching, vacuum blanching, and microwave blanching) on the vacuum oven drying of pegaga leaves was examined in this study. These pre-treatments were selected because they offer distinct advantages that can enhance the drying process and preserve the nutritional quality of the leaves. Pegaga leaves were vacuum oven-dried for 90 minutes at 60 °C at 0.01 MPa. The total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity of pegaga leaves were determined before pre-treatment, after pre-treatment, or before drying and after the drying process. Using the 2,2-diphenyl-1picrylhydrazyl (DPPH) test, the antioxidant activities of the methanolic extract solution were assessed. The Midilli Kucuk model was selected and fitted with the drying data to understand the drying kinetics of pegaga leaves. The results showed that vacuum blanching increased the TPC and TFC of pegaga leaves. The highest DPPH inhibition value was observed in control pegaga leaves after vacuum oven drying. Therefore, the combination of pre-treatments and vacuum oven-dried pegaga leaves may retain their antioxidant and phenolic component content, which would be beneficial to local farmers and fresh produce industries by helping to minimize the loss of quality in dried pegaga leaf manufacturing.